Properties of concrete with polyvinyl alcohol (PVA) coated oil palm shell (OPS) as aggregate - Chai, Willie Wei Shung (Universiti Malaysia Sarawak, UNIMAS, 2012)
Malaysia is the world's second largest palm oil producer which has also subsequently produced a massive amount of by-product. This is evident where the generation of waste oil palm shell (OPS) reached approximately 4.8 million tons in 2010. There is a rise in enviromental concerns on the volume of these agricultural wastes where landfills for waste disposal may not be able to cater for constant accumulation of waste. Past research studies on OPS as concrete aggregate replacement have shown encouraging results. Howecer, the properties of OPS can be further improved to achieve better performance of the resulting concrete. This can be done by treating the raw OPS with PolyVinyl Alcohol (PVA).